NILAI TOLERANSI DALAM INTEGRASI PENDIDIKAN AGAMA ISLAM DAN MULTIKULTURAL SD NEGERI 01 JATILAWANG - Sarah Nur’aeni Khoiriyah; Sunhaji (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe or explain the integration of tolerance values ​​in the integration of Islamic religious education and multicultural education at SD Negeri 01 Jatilawang. This research method uses a qualitative type with a descriptive approach. The data collection methods used are observation, interviews and documentation. The conclusions of this study are: 1) The form of integration of multicultural education in Islamic religious education learning at SD Negeri 01 Jatilawang, there are five forms of multicultural values ​​that are integrated in Islamic religious education learning at SD Negeri 01 Jatilawang, the five forms of values ​​are the values ​​of equality, peace, mutual assistance, democracy and ukhuwah. 2) The implementation of the integration of multicultural education in Islamic religious education learning at SD Negeri 01 Jatilawang is carried out in learning planning, learning implementation, learning evaluation. 3) The impact of the Integration of Islamic Religious Education and Multicultural Education in strengthening tolerance values ​​at SD Negeri 01 Jatilawang, including: a) The creation of a comfortable and conducive learning atmosphere; b) School activities run smoothly and have high tolerance; c) The realization of religious harmony and harmony in differences; d) Avoiding conflict or division; e) The creation of a culture of mutual respect, appreciation and acceptance of differences.